Muscular hypertrophy and growth‐promoting effects in juvenile pejerrey (Odontesthes bonariensis) after oral administration of recombinant homologous growth hormone obtained by a highly efficient refolding process - Sciara, Andres Angel (2011)
Growth hormone (GH) can be orally administrated to fish in order to increase growth rates. Fish growth is characterized by the hyperplasia and hypertrophy of muscle fibre throughout adult life. In this respect, GH could affect directly and indirectly (by growth and metabolic factors) the development and growth of muscle fibres. Recombinant pejerrey GH (r‐pjGH) was expressed in Escherichia coli and refolded in a highly efficient batch dilution system, obtaining 0.1 g L−1 of hormone without protein precipitation during the refolding procedure. Orally administered hormone to pejerrey produced a 30% increase in mean weight and stimulated liver insulin‐like growth factor type I (IGF‐I) mRNA expression after 1 month of treatment. Histological analyses showed that muscle growth was generated mainly by hypertrophy of the fibres. A higher r‐pjGH dose increased muscle fibre hypertrophy but somatic growth was negatively affected probably due to a reduced capacity of generating new fibres.